A Secure Auditable Remote Registry Pattern for IoT Systems - Maña-Gómez, Antonio; Jaime-Rodríguez, Francisco José; Gutiérrez Molina, Lucía (MDPI, 2024)
In software engineering, pattern papers serve the purpose of providing a description of 1 a generalized, reusable solution to recurring design problems, based on practical experience and 2 established best practices. This paper presents an architectural pattern for a secure auditable registry 3 service based on message-oriented middleware to be used in large-scale IoT systems that must 4 provide auditing capabilities to external entities. To prepare the pattern, the direct experience in 5 applying the pattern solution in an industry-funded RD project has been a key aspect because it 6 has allowed us to gain a deep understanding of the problem and the solution, and has contributed 7 to the correctness and real-world applicability of the pattern as described. To further improve the 8 quality of the paper, we have followed the commonly accepted practices in pattern development 9 (including peer reviews) to ensure that the core aspects of the solution are correctly represented 10 and that the description allows it to be applicable to similar problems in other domains, such as 11 healthcare, autonomous devices, banking, food tracing or manufacturing to name a few. The work 12 done in applying this pattern confirms that it solves a recurring problem for IoT systems, but also 13 that it can be adopted in other domains providing an effective solution in order to achieve enhanced 14 auditability capabilities of the target systems. This pattern will be part of a pattern language (i.e. a 15 family of related patterns) that we are developing for transitioning from legacy systems to IoT with 16 an emphasis on security.
Keywords: Seguridad informática; Cybersecurity; Security Engineering; IoT; Patterns; Secure Registries